Labour Left Out: Canada's Failure to Protect and Promote Collective Bargaining as a Human Right - Adams, Roy J. (Canadian Centre for Policy Alternatives, 2006)
[The author] reports on his research into the failure of Canadian governments to protect and promote the collective bargaining rights of both unionized and non-unionized workers in this country. Far from honouring their solemn commitments to the UN’s International Labour Organization, our governments have blatantly and repeatedly violated them. Their many strike-breaking actions and arbitrarily imposed contract settlements have been condemned by the ILO, which has cited Canada as one of the world’s worst violators of basic labour rights. In exposing the appalling anti-labour record of our federal and provincial governments, Adams includes his exchange of correspondence with Canada’s labour ministries on their dismal labour-law policies. –Publisher's summary
http://www.policyalternatives.ca/sites/default/files/uploads/publications/National_Office_Pubs/2006/labour_left_out_toc_preface.pdf
Keywords: Collective bargaining – Canada

Vers une transformation des relations industrielles en Amérique du Nord - Bernatchez, Jean-Claude (Presses de l'Université du Québec, 2006)
Dans un contexte où il semble impossible d’établir, ou encore de maintenir, un régime national de conditions de travail reflétant le niveau de prospérité observable dans les sociétés nord-américaines, la transformation des relations industrielles semble le moyen le plus sûr de rétablir l’équilibre entre le capital et le travail. En s’appuyant sur les fondements historiques des relations industrielles en Amérique du Nord, l’auteur dresse le portrait des syndicalismes américain, canadien et québécois, en tenant compte des lois qui les sous-tendent. Afin d’élaborer un nouveau régime de relations industrielles, il pose les principes à respecter et définit les étapes à franchir en vue d’instaurer de bonnes conditions de travail, garantissant ainsi une meilleure qualité de vie aux citoyens américains et canadiens. –Résumé de l'éditeur
OCLC: 60957589
Keywords: 2000-2099; 21e siècle; Amérique du Nord; Collective bargaining; Collective bargaining North America; Conditions de travail; Industrial relations; Industrial relations North America; North America; Négociation collective; Négociations collectives Amérique du Nord; Relations de travail; Relations industrielles; Relations industrielles Amérique du Nord; Syndicalisme; Travailleurs Amérique du Nord Conditions sociales 20e siècle; Travailleurs Amérique du Nord Conditions sociales 21e siècle; Working class North America Social conditions 21st century; Working class Social conditions; industrial relations

Social Reproduction: Feminist Political Economy Challenges Neo-Liberalism - Bezanson, Kate; Luxton, Meg (McGill-Queen's University Press, 2006)
How the unaccounted costs of neo-liberal policies fall on Canadian women. Using a feminist political economy approach, contributors document the impact of current socio-economic policies on states, markets, households, and communities. Relying on impressive empirical research, they argue that women bear the costs of and responsibility for care-giving and show that the theoretical framework provided by feminist analyses of social reproduction not only corrects the gender-blindness of most economic theories but suggests an alternative that places care-giving at its centre. In this illuminating study, they challenge feminist scholars to re-engage with materialism and political economy to engage with feminism. –Publisher's description. Contents: Introduction: Social Reproduction and Feminist Political Economy / Kate Bezanson and Meg Luxton (pages 3-10) – Feminist Political Economy in Canada and the Politics of Social Reproduction / Meg Luxton (pages 11-44) – Social Reproduction and Canadian Federalism / Barbara Cameron (pages 45-74) – Whose Social Reproduction? Transnational Motherhood and Challenges to Feminist Political Economy / Sedef Arat-Koç (pages 75-92) – Bargaining for Collective Responsibility for Social Reproduction / Alice De Wolff (pages 93-116) – Privatization: A Strategy for Eliminating Pay Equity in Health Care / Marjorie Griffin Cohen and Marcy Cohen (pages 117-144) – Crisis Tendencies in Social Reproduction: The Case of Ontario’s Early Years Plan / Leah F. Vosko (pages 145-172) – The Neo-liberal State and Social Reproduction: Gender and Household Insecurity in the Late 1990s / Kate Bezanson (pages 173-214) – Someone to Watch over You: Gender, Class, and Social Reproduction / Susan Braedley (pages 215-230) – Motherhood as a Class Act: The Many Ways in Which “Intensive Mothering” Is Entangled with Social Class / Bonnie Fox (pages 231-262) – Friends, Neighbours, and Community: A Case Study of the Role of Informal Caregiving in Social Reproduction / Meg Luxton (pages 263-92 ).

Push! The Struggle for Midwifery in Ontario - Bourgeault, Ivy Lynn (McGill-Queen's University Press, 2006)
In the 1980s there were few midwives in Canada and their practice was neither legal nor officially recognized. Ontario midwives and their supporters pushed to integrate midwifery into provincial health care systems and by 1993 had established an internationally renowned model. Ivy Lynn Bourgeault analyses the struggle to professionalize midwifery in the context of the negotiations between women, as both consumers and providers of health care, and the state. Push! offers a historical account of the forces behind the integration of midwifery in Ontario, including public interest in funding midwifery services and the impact of political lobbying. Bourgeault also explores the specific features of Ontario's respected model, including the use of independent practitioners, funding for a self-regulatory college, a university-based education program, and the provision of midwifery care in both home and hospital settings. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/pushstruggleform0000bour
Keywords: Government policy; History; Home childbirth; Midwifery; Midwives; Ontario; Political aspects

The Hanging of Angélique: The Untold Story of Canadian Slavery and the Burning of Old Montréal - Cooper, Afua (University of Georgia Press, 2006)
During the night of April 10, 1734, Montréal burned. Marie-Joseph Angélique, a twenty-nine-year-old slave, was arrested, tried, and found guilty of starting the blaze that consumed forty-six buildings. Suspecting that she had not acted alone and angered that she had maintained her innocence, Angélique's condemners tortured her after the trial. She confessed but named no accomplices. Before Angélique was hanged, she was paraded through the city. Afterward, her corpse was burned. Angélique, who had been born in Portugal, faded into the shadows of Canadian history, vaguely remembered as the alleged arsonist behind an early catastrophic fire. The result of fifteen years of research, [this book] vividly tells the story of this strong-willed woman. Afua Cooper draws on extensive trial records that offer, in Angélique's own words, a detailed portrait of her life and a sense of what slavery was like in Canada at the time. Predating other first-person accounts by more than forty years, these records constitute what is arguably the oldest slave narrative in the New World. Cooper sheds new light on the largely misunderstood or ignored history of slavery in Canada. She refutes the myth that Canada was a haven at the end of the Underground Railroad. Cooper also provides a context for Canada in the larger picture of transatlantic slavery while re-creating the tragic life of one woman who refused to accept bondage. –Publisher's description
Available at Internet Archive to readers with print disabilities: https://archive.org/details/hangingofangeliq0000coop OCLC: 71812881
Keywords: 18e siècle. Esclaves; 18e siècle. Fires. Slaves; 18e siècle. Noires; 18th century. Esclaves; Biographies. Esclavage; Biographies. Incendies; Biography. Fires; Canada; Commerce; Histoire; History; Montréal; Québec (Province); Slaves

Globalization and the Future of Labour Law - Craig, John D. R.; Lynk, Michael (Cambridge University Press, 2006)
How are national and international labour laws responding to the challenge of globalization as it re-shapes the workplaces of the world? This collection of essays by leading legal scholars and lawyers from Europe and the Americas was first published in 2006. It addresses the implications of globalization for the legal regulation of the workplace. It examines the role of international labour standards and the contribution of the International Labour Organization, and assesses the success of the European experiment with continental employment standards. It explores the prospects for hemispheric co-operation on labour standards in the Americas, and deals with the impact of international labour standards on the rights of women and migrant workers. As the nature and organization of work around the world is being decisively transformed, new regional and international institutions are emerging that may provide the platform for new labour standards, and for protecting existing ones. –Publisher's description
OCLC: 70899362
Keywords: Americas; Amériques; Droit du travail; European Union; Futur; Globalization; International Labour Organization; International labour law; Labor laws and legislation; Labor laws and legislation; International; Labour law; Labour standards; Mondialisation; Normes de travail; Normes internationales; Organisation internationale du travail; Travail (Droit international); UE/CE Union européenne

Women and Their Work in Upper Canada - Errington, Elizabeth Jane (Canadian Historical Association, 2006)
OCLC: 1023393307

Red Light Neon: A History of Vancouver's Sex Trade - Francis, Daniel (Subway, 2006)
"This book is a history of hypocrisy." So begins Daniel Francis, BC's leading popular historian, as he explores the colourful and ultimately tragic story of prostitution in Vancouver. He writes: "The city's political and social leaders consistently have treated prostitutes as pariahs whose presence was tolerated, sometimes exploited, but never approved. All the while, the authorities collected millions of dollars in fines and licence fees from businesses that everyone knew were, and are, fronts for the sex trade." Working in long overlooked archives and drawing on personal interviews, Francis shows how in some ways commercial sex has been both a reflection and a result of Vancouver's essential character, with its tolerant social mores, ethnic diversity–and political opportunism. It's a tale that takes in mayors and masseuses, police chiefs and pimps, judges and johns. Francis explains: "Sex workers have never lacked for customers. What they have lacked is a secure place to conduct their business. A vast off-street sex trade flourished while police, at the urging of politicians vowing to purify the city, concentrated their attention on the comparatively small number of street prostitutes who worked out in the open. Because they were considered a nuisance, these sex workers were hounded from street to street and neighbourhood to neighbourhood [... These efforts salved the conscience of the morally righteous, but each attempt to discourage prostitution simply forced women to work in increasingly dangerous circumstances." The end result, ultimately, was the tragedy of the Missing Women–murdered sex workers from the Downtown Eastside–and the sensational criminal case that followed. –Publisher's description
Keywords: Prostitution – British Columbia – Vancouver – History

Working on Screen: Representations of the Working Class in Canadian Cinema - Khouri, Malek; Varga, Darrell (University of Toronto Press, 2006)
As themes in film studies literature, work and the working class have long occupied a peripheral place in the evaluation of Canadian cinema, often set aside in the critical literature for the sake of a unifying narrative that assumes a division between Québécois and English Canada's film production, a social-realist documentary aesthetic, and what might be called a 'younger brother' relationship with the United States. In Working on Screen, contributors examine representations of socio-economic class across the spectrum of Canadian film, video, and television, covering a wide range of class-related topics and dealing with them as they intersect with history, political activism, globalization, feminism, queer rights, masculinity, regional marginalization, cinematic realism, and Canadian nationalism. Of concern in this collection are the daily lives and struggles of working people and the ways in which the representation of the experience of class in film fosters or marginalizes a progressive engagement with history, politics, and societies around the world. Working on Screen thus expands the scholarly debates on the concept of national cinema and builds on the rich, formative efforts of Canadian cultural criticism that held dear the need for cultural autonomy. – Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/workingonscreenr0000unse

Paths to Union Renewal: Canadian Experiences - Kumar, Pradeep; Schenk, Christopher Robert (Broadview Press, 2006)
This book focuses on the efforts and progress of union revitalization and organizing, and documents the renewal initiatives undertaken by unions in Canada. Unions, separately or in coalition with other unions or social groups, have begun to re-examine the basis of their organization and activity in the face of a harsher economic and political climate. Signs of union renewal include increased rank-and-file participation in the life of the union, increased democratic decision-making, evidence of new horizontal union structures, the development of a worker-centred societal vision, and a new emphasis on organizing both internally and externally. Paths to Union Renewal addresses a subject of considerable political and social importance about which there have been a number of debates. A key impetus for this re-examination has originated in the United States where decades-long union decline has engendered new ideas adopted by a number of unions and the national central labour body the AFL-CIO. This in turn has led to debates on renewal strategies in Western Europe and Anglo-Saxon countries from Britain to Australia. Despite this, little detailed research of the processes, structures, and implications of union renewal has been undertaken across Canada. Paths to Union Renewal fills this gap by critically examining union renewal in a variety of unions, providing a basis for informed discussion and debate on the role and place of trade unions in contemporary society. –Publisher's description
Keywords: British Columbia Federation of Labour. Organizing Institute; British Columbia Government and Service Employees Union (BCGEU); Canadian Auto Workers (CAW); Canadian Union of Public Employees (CUPE); Communications; Energy and Paperworkers Union of Canada (CEP); Community unionism; Labor Unions; Labor movement; Organizational change; United Food and Commerical Workers (UFCW); United Steelworkers (USW)

Bloodletting & Miraculous Cures: Stories - Lam, Vincent. (Doubleday Canada, 2006)
Bloodletting & Miraculous Cures is a collection of mature and intricate stories connected through the relationships that develop among a group of young doctors as they move from the challenges of med school to the intense world of emergency rooms, evac missions, and terrifying new viruses. –Publisher's description. Contents: How to get into medical school, part I – Take all of Murphy – How to get into medical school, part II – Code clock – A long migration – Winston – Eli – Afterwards – An insistent tide – Night flight – Contact tracing – Before light – Glossary of terms – Acknowledgements.
Keywords: Doctor; Medical Students; Physicians; Short Stories; White-collared work

Red Travellers: Jeanne Corbin and Her Comrades - Lévesque, Andrée (McGill-Queen's University Press, 2006)
Jeanne Corbin typifies the female militants of the first generation of Canadian Communists. Andrée Lévesque's powerful account of the experiences of Corbin and her female comrades reveals the essential role women played in the movement. Levesque also shows that, despite some efforts to construct egalitarian gender relations, these women subordinated gender issues to the class struggle. Corbin's red itinerary began when she joined the Young Communist League in Edmonton. She later held party posts across the country through her involvement with The Worker in Toronto, a French communist paper in Montreal, the Workers' Cooperative in Timmins, and a lumbermen's strike in Abitibi - where she was jailed for taking part in a protest. She died of tuberculosis in London, Ontario, in 1944. Levesque relies on a wide range of sources to provide a unique exploration of Canadian labour and social history. –Publisher's descriptioin
Book available at Internet Archive to people with print disabilities: https://archive.org/details/redtravellersjea0000leve OCLC: 778049214

Social Reproduction: Feminist Political Economy Challenges Neo-Liberalism - Luxton, Meg; Bezanson, Kate (McGill-Queen's University Press, 2006)
Using a feminist political economy approach, contributors document the impact of current socio-economic policies on states, markets, households, and communities. Relying on impressive empirical research, they argue that women bear the costs of and responsibility for care-giving and show that the theoretical framework provided by feminist analyses of social reproduction not only corrects the gender-blindness of most economic theories but suggests an alternative that places care-giving at its centre. In this illuminating study, they challenge feminist scholars to re-engage with materialism and political economy to engage with feminism. – Publisher's description
OCLC: 649927976
Keywords: Canada; Discrimination à l'égard des femmes Canada; Feminist economics; Feminist economics Canada; Feminist theory; Feminist theory Canada; Femmes Canada Conditions sociales; Femmes Canada Conditions économiques; SOCIAL SCIENCE Feminism & Feminist Theory; SOCIAL SCIENCE Sociology General; Sex discrimination against women; Sex discrimination against women Canada; Théorie féministe Canada; Women Canada Economic conditions; Women Canada Social conditions; Women Economic conditions; Women Social conditions; Économie féministe Canada

Canadian Working-Class History: Selected Readings - MacDowell, Laurel Sefton; Radforth, Ian Walter (Canadian Scholars' Press, 2006)
[This book updates] recent and classic scholarship on the history, politics, and social groups of the working class in Canada. Some of the changes...in the new edition include better representation of women scholars and nine provocative and ground-breaking new articles on racism and human rights; women's equality; gender history; Quebec sovereignty; and the environment. –Publisher's description
https://canadianscholars.ca/book/canadian-working-class-history-3rd-edition/
Keywords: Equality; History; Human rights; Labor Unions; Labor movement; Labour; Racism; Social history; Women; Working class; labour rights

Working Class Culture and the Development of Hull, Quebec, 1800-1929 - Martin, Michael (J. Bernier, 2006)
...This [book], most decidedly, is not only the narrative of the prominent citizens in the history of Hull. Rather, it is the story of thousands of virtually unknown men, women, and children of the working class of Hull, Quebec. Among many others, it’s the story of James McConnell, a worker from Nova Scotia, hired by Philemon Wright in Quebec City in 1801. It’s the story of Luther Colton, a carpenter from New York, who came to Hull in 1802. It’s the story of Joseph Delorme, one of the first French Canadians to be hired by Philemon Wright to work in his shanties, just to give three examples of normally unnamed workers. This study of the ordinary people of Hull reflects an agenda that emerged in the last half of the 20th century when historians came to see that “the real task of history in our time is to recreate, appreciate and analyze the full spectrum of past societies; that means, pre-eminently to attempt to understand the lives of the working people, the great mass of any society,” rather than merely the politicians and elites who governed past societies. This book also studies the workers who helped the workers of Hull forge an awareness of themselves as a class in a self-conscious attempt to improve the lot of ordinary working people. –Author's preface
https://epe.lac-bac.gc.ca/100/200/300/michael_martin/working_class/index.html?nodisclaimer=1 OCLC: 319895101
Keywords: History; Hull (Gatineau; Québec) History; Hull (Gatineau; Québec) Social conditions; Québec Gatineau Hull; Social conditions; Working class; Working class Hull (Gatineau; Québec) History

Apprivoiser le syndicalisme en milieu universitaire: histoire du syndicat genéral des professeurs et professeures de l'Université de Montréal - Rouillard, Jacques (Boréal, 2006)
Un syndicat de professeurs d’université n’est pas un syndicat comme les autres. L’individualisme inhérent au travail et à la culture professorale a toujours contribué à rendre plusieurs d’entre eux méfiants et plutôt réservés face à la solidarité syndicale. Chez les professeurs, le « nous » syndical s’est graduellement construit, par étapes, parfois dans la tourmente et la division. C’est ce cheminement des universitaires, cet «apprivoisement» du syndicalisme, qui est l’objet de ce volume. La conscience syndicale chez les professeurs commence véritablement à prendre racine avec la création du Syndicat des professeurs en 1966. Elle aboutit à la formation du SGPUM en 1972 et à son accréditation trois ans plus tard. Dans les années 1980 et 1990 l’utilité du syndicalisme ne fait plus de doute chez les professeurs, frappés par de faibles augmentations salariales, quand ce n’est pas des gels et des récupérations. Dans les années 2000, leur solidarité se renforce avec l’objectif de rattrapage des conditions de travail qui va culminer avec la première grève des professeurs en hiver 2005. Jacques Rouillard propose ici un historique de quarante ans de vie syndicale et de plus de cinquante ans de vie associative. Soucieux également d’insérer l’évolution du syndicat dans la trame générale de l’histoire du syndicalisme québécois, il accorde une large place dans cet historique aux négociations des syndicats des secteurs public et parapublic. –Résumé de l'éditeur
OCLC: 255962035

Working in a Global Era: Canadian Perspectives - Shalla, Vivian (Canadian Scholars Press, 2006)
This progressive new reader examines work in a global era. It is an ideal text for sociology of work and labour courses across Canada. This book will also be relevant to a wide range of courses in labour studies and industrial relations programs in Canada." "Divided into eight key parts with a total of 16 essential readings, this volume covers a great deal of ground: Fordist and post-Fordist methods of work organization; labour markets in transition; working in the free-trade zones; migration, transnationalism, and domestic work; neo-liberalism and the dismantling of the welfare state; education, training, and skills in a knowledge-based economy; and the labour movement in transition. All major issues surrounding work in Canada are covered. Book jacket. –Publisher's description
Keywords: Labor – Canada – Textbooks

Home Economics: Nationalism and the Making of 'Migrant Workers' in Canada - Sharma, Nandita Rani (University of Toronto Press, 2006)
Home Economics is an urgent and much-needed reminder that society must pay careful attention to how nationalist ideologies construct ‘homelands’ that essentially leave the vast majority of the world's migrant peoples homeless. A massive shift has taken place in Canadian immigration policy since the 1970s: the majority of migrants no longer enter as permanent residents but as temporary migrant workers. In Home Economics, Nandita Sharma shows how Canadian policies on citizenship and immigration contribute to the entrenchment of a system of apartheid where those categorized as migrant workers live, work, pay taxes and sometimes die in Canada but are subordinated to a legal regime that renders them as perennial outsiders to nationalized Canadian society. In calling for a no borders policy in Canada, Sharma argues that it is the acceptance of nationalist formulations of home informed by racialized and gendered relations that contribute to the neo-liberal restructuring of the labour market in Canada. She exposes the ideological character of Canadian border control policies which, rather than preventing people from getting in, actually work to restrict their rights once within Canada. Home Economics is an urgent and much-needed reminder that in today's world of growing displacement and unprecedented levels of international migration, society must pay careful attention to how nationalist ideologies construct homelands that essentially leave the vast majority of the world's migrant peoples homeless. –Publisher's description
Available at Internet Archive to readers with print disabilities: https://archive.org/details/homeeconomicsnat0000shar OCLC: 61427334
Keywords: Ausländischer Arbeitnehmer; Canada; Canada Emigration and immigration Government policy; Canada Émigration et immigration Politique gouvernementale; Capitalism; Capitalisme; Einwanderung; Electronic books; Emigration and immigration Government policy; Foreign workers Government policy; Foreign workers Government policy Canada; Globalization; Kanada; Kapitalismus; Mondialisation; Travailleurs étrangers Politique gouvernementale Canada; capitalism; globalism

The Struggle Against Wage Controls: The Saint John Story, 1975-1976 - Vair, George; Canadian Committee on Labour History (Canadian Committee on Labour History, 2006)
In October 1976 one million Canadian workers walked off the job to protest the wage controls imposed by Prime Minister Pierre Elliott Trudeau. In a memorable personal account of this historic general strike, Saint John labour activist George Vair recalls how workers in one New Brunswick city mobilized to defend themselves and their unions and defeat the unpopular program. –Publisher's description
https://archive.org/details/struggleagainstw0000vair
Keywords: General Strike; Saint John; N.B.; 1976; Government policy; History; Labor movement; Strikes and lockouts; Wages

Precarious Employment: Understanding Labour Market Insecurity in Canada - Vosko, Leah F. (McGill-Queen's University Press, 2006)
This interdisciplinary volume offers a multifaceted picture of precarious employment and the ways in which its principal features are reinforced or challenged by laws, policies, and labour market institutions, including trade unions and community organizations. Contributors develop more fully the concept of precarious employment and critique outmoded notions of standard and nonstandard employment. The product of a five-year Community-University Research Alliance, the volume aims to foster new social, statistical, legal, political, and economic understandings of precarious employment and to advance strategies for improving the quality and conditions of work and health. –Publisher's description
Keywords: Industrial hygiene; Labor Unions; Labor laws and legislation; Labor market; Temporary employment